2017 IEEE 25th International Requirements Engineering Conference (RE) 2017
DOI: 10.1109/re.2017.28
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study on a Specification Approach Using Activity Diagrams in Requirements Documents

Abstract: Rising complexity of systems has long been a major challenge in requirements engineering. This manifests in more extensive and harder to understand requirements documents. At the Daimler AG, an approach is applied that combines the use of activity diagrams with natural language specifications to specify system functions. The approach starts with an activity diagram that is created to get an early overview. The contained information is then transferred to a textual requirements document, where details are added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In a previous work, we defined and analyzed different types of quality issues that arise when activity diagrams are used in requirements documents for the specification of functions [14]. One of the quality issues, we identified, are redundant elements.…”
Section: Redundant Elements In Activity Diagramsmentioning
confidence: 99%
“…In a previous work, we defined and analyzed different types of quality issues that arise when activity diagrams are used in requirements documents for the specification of functions [14]. One of the quality issues, we identified, are redundant elements.…”
Section: Redundant Elements In Activity Diagramsmentioning
confidence: 99%
“…1. In a former study, we investigated these issues in detail [13]. While some of these issues can be resolved [14], some of the other issues originate from the currently used textual representation.…”
Section: /mentioning
confidence: 99%
“…Also we received only a relatively small number of answers. We combined our survey with another study on quality issues that arise from using activity diagrams and their textual representations side by side [13]. Thus, all participants of this survey also participated in the previous study.…”
Section: Threats To Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, we have shown that this is a potential source for inconsistencies and quality issues in the requirements specifications [7]. Moreover, best practices and guidelines for when and how to use graphical or textual representations are missing.…”
Section: Introductionmentioning
confidence: 99%